Integrasi Nilai-Nilai Pendidikan Ibadah dalam Al-Qur'an dan Hadis: Studi Analisis Konten terhadap Nash-Nash Pendidikan : Penelitian - Atsira, Luthfia; Ayani, Nabilah Ikrimah; Syafruddin, Syafruddin; Zulheldi, Zulheldi; Rehani, Rehani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses the integration of religious education values ​​in the Qur'an and Hadith through a content analysis of texts related to the development of religious education. Worship education is seen as the main foundation in the formation of a Muslim personality that is faithful, pious, and has noble morals. This study explains the concept of worship comprehensively, starting from its definition, purpose, and the spiritual, moral, and social dimensions it contains. The discussion includes verses of the Qur'an such as Surah Al-Fatihah verse 5, Surah Luqman verse 17, Surah Thaha verse 132, and Surah Al-Baqarah verse 183, as well as several hadiths that emphasize the importance of habituating worship, exemplary behavior, and a gradual approach in education. The analysis shows that the methods of religious education in the Qur'an and Hadith emphasize aspects of role models, dialogue, habituation, internalization of values, and adaptation to the development of students. The results of this study confirm that religious education should not focus solely on ritual aspects, but also on character development through the values ​​of monotheism, discipline, patience, and social responsibility. Therefore, religious education needs to be holistically integrated into the Islamic education system to shape a generation with morals and spiritual awareness.